2004
DOI: 10.1038/nature02212
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically driven ATP synthesis by F1-ATPase

Abstract: ATP, the main biological energy currency, is synthesized from ADP and inorganic phosphate by ATP synthase in an energy-requiring reaction. The F1 portion of ATP synthase, also known as F1-ATPase, functions as a rotary molecular motor: in vitro its gamma-subunit rotates against the surrounding alpha3beta3 subunits, hydrolysing ATP in three separate catalytic sites on the beta-subunits. It is widely believed that reverse rotation of the gamma-subunit, driven by proton flow through the associated F(o) portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
393
2
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 514 publications
(409 citation statements)
references
References 21 publications
6
393
2
4
Order By: Relevance
“…The stator a 3 b 3 ring has the intrinsic cooperativity necessary to achieve rotary catalysis among the three catalytic sites. However, this result is not inconsistent with the observations that the rates and equilibriums of the F 1 reactions are controlled by the rotary angle of the c-subunit (14,18,(25)(26)(27). Without the c-subunit, the rate and efficiency of the unidirectional rotary catalysis was distinctly lower than that for F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fcontrasting
confidence: 54%
See 1 more Smart Citation
“…The stator a 3 b 3 ring has the intrinsic cooperativity necessary to achieve rotary catalysis among the three catalytic sites. However, this result is not inconsistent with the observations that the rates and equilibriums of the F 1 reactions are controlled by the rotary angle of the c-subunit (14,18,(25)(26)(27). Without the c-subunit, the rate and efficiency of the unidirectional rotary catalysis was distinctly lower than that for F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fcontrasting
confidence: 54%
“…Thus, it was proposed that interactions with the c-subunit control the conformational and catalytic states of each b-subunit to sequentially generate torque (24). The single-molecule manipulation experiments showed that by controlling the rotary angle of the c-subunit alone, the rate and equilibrium of the ATP hydrolysis/synthesis reaction on F 1 can be modulated and even reversed, and reinforced the contention (14,18,(25)(26)(27). These results caused the elevation of the c-subunit to the position of a ''dictator,'' completely controlling the reaction catalyzed by F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fmentioning
confidence: 95%
“…So in FATPase a synthesis of one ATP also drives 120 degrees rotation, which, however, requires a movement of 4 subunits c, hence 4 protons (Van Walraven et al 1996;Panke and Rumberg 1997;Stock et al 1999;Ferguson 2000;Seelert et al 2000;Stahlberg et al 2001). In the case of F-ATPase rotation and ATP synthesis is driven by trans-membrane delta pH, but it should be noted that both enzymes can work in both directions depending on the conditions Itoh et al 2004;Rondelez et al 2005;Feniouk et al 2007;Nakano et al 2008). Another difference between these related rotary engines is that whereas the c ring of the F-ATPase is built from identical c subunits, each having two trans-membrane alpha helices (Dmitriev et al 1999;Fillingame et al 2000), the c ring in V-ATPase consist of 4 c subunits and one copies of c' and c" subunits each (Hirata et al 1997;Powell et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications may add or remove barriers to the rotation not present in the native system. Consequently, the reported rotation rates vary greatly in such studies, depending on the gene-engineered construct and the details of the artificial environment of the enzyme (Panke and Rumberg 1997;Masaike et al 2000;Itoh et al 2004;Imamura et al 2005;Adachi et al 2007;Takeda et al 2009). Such studies are not possible on a native enzyme in a native membrane, but since the ATP/rotation stoichiometry is known, one could assay the inorganic phosphate liberated from ATP hydrolysis by V-ATPase in unit time and relate it to the concentration of V-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For example, groundbreaking studies in single-molecule visualization revealed many aspects of the dynamics of F1-ATPase rotary motor, including rotation rates and details of the mechanochemical reaction cycle. [4][5][6][7] Several studies also probed the behavior of mechanoenzymes such as myosin, kinesin and dynein; most prominent were those techniques that measured the step size and force exerted by these proteins as they travel along actin filaments or microtubules. [8][9][10][11][12][13][14][15][16][17][18][19] Early work in single-molecule bioscience also included measurements of individual transcribing molecules of bacterial RNA polymerase, [20][21][22] and more recent studies with this enzyme were carried out to greater precision with instrumentation capable of making real time measurements with spatial resolution approaching one base pair.…”
Section: Introductionmentioning
confidence: 99%